Exploratory transcriptomic analysis of low-grade oral epithelial dysplasia and oral squamous cell carcinoma in Chilean patients - Mateus José Dutra; Patricio Miranda Cortes; Valentina Fernanda Fernández Díaz; Mauricio Alejandro Sáez Venegas; Sebastián Morales-Pison; Wilfredo Alejandro González-Arriagada; Ricardo Fernández-Ramires; Daniela Adorno-Farias (Molecular Biology Reports, 2026)

Tolerance of larval and juvenile tambaqui (Colossoma macropomum) to nitrogenous compounds - Raphael Brito Dos Santos; Paulo Adelino de Medeiros; Roberta de Paula Anjos; Sarah Lia de Araújo Mota; Cláudia Cristina de Souza Sena; Fernanda Miranda de Andrade; Valdelira Lia Araújo Fernandes; Elizabeth Gusmão Affonso (Chemosphere, 2026)

Endoplasmic reticulum stress is associated with cardiac effects of bisphenol S independently of a high-fat diet - Beatriz Alexandre-Santos; Guilherme dos Santos Reis; Luiza Mazzali Ferraz; Maria Eduarda Lima da Silva; Gabriel Ferreira Lima; Fernanda Carla Ferreira Brito; Milena Barcza Stockler-Pinto; Antonio Claudio Lucas da Nóbrega; Leandro Miranda-Alves; D’Angelo Carlo Magliano; Eliete Dalla Corte Frantz (Histochemistry and Cell Biology, 2026)
Obesity and endocrine disruptors (EDs) promote endoplasmic reticulum (ER) stress, a mechanism associated with cardiovascular diseases. Among EDs, BPS is widely used in consumer products. Whether BPS promotes cardiac ER stress, either alone or combined with a high-fat diet, remains unclear. Male C57BL/6 mice were assigned to a standard chow diet (SC—15 kJ/g), SC+BPS (SCB), high-fat diet (HF—21 kJ/g), or HF+BPS (HFB), receiving BPS (25 μg/kg/day) through their drinking water for 12 weeks. Body mass (BM), lipid profile, cardiac risk ratio, heart mass, and cardiac ER stress, apoptosis, and oxidative stress markers were assessed. A high-fat diet intake increased BM gain, total cholesterol, cardiac risk ratio, and heart mass compared with standard chow diet intake. These parameters were higher in the SCB group than in the SC group. ER stress (GRP78, ATF4, and CHOP protein expression), pro-apoptotic (BAX protein expression and caspase 3 immunostaining), and pro-oxidative (NOX2 and NOX4 protein expression as well as MDA levels) markers were elevated in high-fat diet-fed animals compared with standard chow-fed animals. BPS exposure increased these parameters in standard chow-fed animals. High-fat diet intake reduced BCL2 expression and increased the BAX/BCL2 ratio compared with standard chow diet intake. BPS exposure increased BCL2 expression in standard chow-fed animals and increased the BAX/BCL2 ratio in high-fat diet-fed animals. ER stress appears to play a role in the cardiac effects of BPS. BPS exposure exacerbated the high-fat diet-induced pro-apoptotic response.

Assessment of cytotoxicity and genomic instability induced by coal-derived nanoparticles in V79 and HaCaT Cells - Alvaro Miranda-Guevara; Wilner Martínez-López; Grethel León-Mejía; Ornella Fiorillo Moreno; Leonardo Pacheco-Londoño; Julian Rodríguez Tapia; Fredy Jose Torres Cantillo; Maria Fernanda Palma; Paola Hernández; Pablo Liddle; Burix Mechoso; Miriam López; et al. (Archives of Toxicology, 2026)
Coal is a major global energy resource, but its extraction raises significant environmental and health concerns. Mining activities release large amounts of particulate matter, including nanoparticles (NPs), into the environment. These NPs are hazardous due to their content of polycyclic aromatic hydrocarbons (PAHs), metals, oxides, and other compounds capable of disrupting cellular and molecular processes. This study evaluated the cytotoxic and genotoxic effects of coal-derived NPs on V79 and HaCaT cell lines, focusing on their impact on DNA stability and the mechanisms responsible for cellular damage. NPs were isolated using an acid-based separation method and applied to cells at concentrations of 50, 150, and 300 μg/mL. Atomic force microscopy (AFM) provided topographical characterization, while dynamic light scattering (DLS) confirmed their tendency to agglomerate. Scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS) confirmed NP morphology and elemental composition, including carbon, oxygen, iron, calcium, silicon, aluminum, and copper. Cytotoxicity was assessed using resazurin and sulforhodamine B assays, and genotoxicity was evaluated using the comet assay, micronucleus test, and γH2AX immunostaining. Results showed a clear dose-dependent effect, with coal NPs inducing genomic instability and increased cell mortality, mainly through apoptosis. These findings highlight the importance of characterizing coal-derived NPs to better assess their environmental and health risks, particularly regarding respiratory diseases.

Canopy structure, dry matter intake and performance of Holstein × Gyr cows (Bos taurus taurus L. × Bos taurus indicus L.) under rotational stocking in Urochloa spp. pastures - Natalia Avila Soares; Carlos Augusto de Miranda Gomide; Patrícia do Rosário Rodrigues; Domingos Sávio Campos Paciullo; Mirton José Frota Morenz; Angelo Herbet Moreira Arcanjo; Fernando Antônio de Souza; Fernanda de Kássia Gomes; Pedro Drummond Rodrigues; Ângela Maria Quintão Lana (Tropical Animal Health and Production, 2026)
Pasture-based dairy systems require well-adapted forage cultivars and appropriate grazing management to sustain milk production while maintaining favorable sward structure. The objective of this study was to evaluate the performance of Holstein × Gyr crossbred cows and the productive and structural characteristics of Paiaguás grass pasture ( Urochloa brizantha cv. BRS Paiaguás) and Ipyporã grass pasture ( Urochloa brizantha × Urochloa ruziziensis cv. BRS Ipyporã), under rotational stocking during two rainy season. For the agronomic variables, a completely randomized design was adopted in a split-plot design: two grasses and three experimental phases, with twelve paddocks evaluated per phase. The arrangement for milk yield and milk composition was the complete switchback trial, and for dry matter intake, it was the cross-over. Paiaguás grass showed greater herbage mass, accumulation and herbage accumulation rate. Ipyporã grass showed a greater leaf: stem ratio (1.54 vs. 1.02) and greater volumetric density (127.45 vs. 108.15 kg DM cm ha − 1 ). Milk yield did not differ between cultivars or experimental phases with an average value of 107.65 L ha − 1 day − 1 ). Stocking rate was higher in Paiaguás grass pasture compared with Ipyporã grass (7.71 vs. 6.90 AU ha − 1 ). Dry matter intake differed between cultivars only in phase 2, when it was higher for Ipyporã grass compared with Paiaguás grass (2.21 vs. 1.97% of body weight, respectively). Both cultivars supported a great milk yield when managed with 41 cm pre-grazing height for cv. BRS Ipyporã and 63 cm for cv. BRS Paiaguás, and 50% defoliation.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Sesquiterpene-rich n -hexane extracts from Aspidosperma subincanum Mart.: anti- Xanthomonas citri activity, acetylcholinesterase inhibition and insights into molecular docking - Hindenburg C. G. da Costa; Jaciel G. dos Santos; Cassia C. Fernandes; Cibele S. Minafra; Anna L. O. Santos; Daniela S. Gonçalves; Carlos H. G. Martins; Matheus R. S. Melo; Fernanda F. Noronha; Denise C. Tavares; Yan R. Robles; Antônio E. M. Crotti; et al. (Natural Product Research, 2026)

Sex-specific cardiac responses to subacute exposure to tributyltin in rats - Ana Beatriz Araújo Mendes; Nadia Alice Vieira Motta; Gabriel Ferreira Lima; Lis Jappour Autran; Stephani Correia Brazão; Nikolas Cunha de Assis Pereira; Ana Rebecca da Silveira de Souza; Beatriz Alexandre-Santos; D'Angelo Carlo Magliano; Leandro Miranda-Alves; Fernanda Carla Ferreira Brito (Chemico-Biological Interactions, 2026)

Assessing long-term stability of arsenic immobilization by iron-impregnated biochar under simulated irrigation and accelerated aging - Xu Liao; Raúl Miranda-Avilés; Alma Hortensia Serafin Muñoz; Jesús Horacio Hernández Anguiano; María Jesús Puy-Alquiza; Saugata Datta; Merced Martínez Rosales; Ignacio René Galindo Esquivel; Daniela Moncada; Luisa Fernanda Rueda‑Garzon; Xiaoxiao Zha; Elcia Margareth Souza Brito; et al. (Environmental Geochemistry and Health, 2026)

Short-term effects of converting degraded pasture to silvopastoral systems on soil carbon and nitrogen dynamics in a Brazilian Oxisol - Róberson Machado Pimentel; Dilermando Miranda da Fonseca; Emanuelle Mercês Barros Soares; Sílvio Nolasco de Oliveira Neto; Geraldo Fábio Viana Bayão; Rafael da Silva Teixeira; Igor Lima Bretas; Wesley dos Santos Souza; Rafael Gonçalves Tonucci; Bruno Grossi Costa Homem; Fernanda Helena Martins Chizzotti (Geoderma Regional, 2026)

Validation of SMAP, SMOS, and ESA CCI SM soil moisture products in a seasonally dry tropical forest - Cloves Vilas Boas dos Santos; Josiclêda Domiciano Galvíncio; Rodrigo de Queiroga Miranda; Herica Fernanda de Sousa Carvalho; Alzira Gabrielle Soares Saraiva Souza; Inajá Francisco de Sousa; Magna Soelma Beserra de Moura (Journal of South American Earth Sciences, 2026)

Cashew nut protein concentrate as a potential ingredient for the emerging alternative protein industry - Jéssica Silva do Carmo; José Diogo da Rocha Viana; Arthur Claudio Rodrigues de Souza; Kelvi Wilson Evaristo Miranda; Celli Rodrigues Muniz; Lorena Mara Alexandre e Silva; Matheus Dias de Carvalho; Ana Carla Kawazoe Sato; Daniele Maria Alves Teixeira Sá; Wellington da Silva Oliveira; Fernanda Furlan Gonçalves Dias; Ana Paula Dionísio (Food Chemistry, 2025)

Climate change–induced terrestrial matter runoff may decrease food web production in coastal ecosystems - Owen F. Rowe; Joanna Paczkowska; Andreas Brutemark; Sonia Brugel; Sachia J. Traving; Robert Lefébure; Fernanda Miranda; Liudmyla Guleikova; Evelina Griniene; Iveta Jurgensone; Pär Byström; Lasse Riemann; et al. (Limnology and Oceanography, 2025)
Climate change is projected to cause elevated precipitation in northern Europe, leading to increased runoff of terrestrial matter to coastal areas. The consequences for food web production and ecosystem function remain unclear. A mesocosm experiment was performed to investigate the impacts of elevated terrestrial matter input, using a natural plankton community from the northern Baltic Sea with added young‐of‐the‐year perch as planktivorous top consumer. Addition of terrestrial matter caused water browning and increased dissolved organic carbon and inorganic nutrient concentrations. Phytoplankton primary production showed a negative response to terrestrial matter due to decreased light availability, while heterotrophic bacterial production increased. The trophic balance, calculated as the difference between primary production and heterotrophic bacterial production, indicated that net‐heterotrophy was triggered by terrestrial matter enrichment. Primary production was identified as the main basal energy source for fish. Addition of terrestrial matter reduced the food web efficiency, calculated as the ratio between fish production and basal production (primary production + heterotrophic bacterial production). Furthermore, stable isotope analysis of seston and fish indicated that the added terrestrial matter was not efficiently incorporated in the food web and only marginally altered the food web trophic positions. The results suggest that the main food chain consisted of phytoplankton, mesozooplankton, and fish, and that the ecosystem production was overall light driven. Under a changing climate, several negative effects can be expected, including a poorer light climate, reduced ecosystem production and net‐heterotrophy. These alterations have potentially significant consequences for ecosystem functioning, fish production, and thus ecosystem services.

White lab coat syndrome in dogs: Owners’ perception - Anna Julia Bessa Fernandes; Debora Azevedo Borges; Isabelle Vilela Bonfim; Fernando Rocha Miranda; Fernanda da Silva Freitas Campos; Clara Rodrigues Dutra; Ingrid Lins Raquel De Jesus; Taynara Monsores Silva; Yara Peluso Cid (Journal of Veterinary Behavior, 2025)

Skin transcriptome and microbiome profiling are associated with Atlantic salmon resistance/susceptibility to sea lice infestation - Valentina Valenzuela-Muñoz; Cristian Gallardo-Escárate; María Fernanda Morales; Diego Valenzuela-Miranda; Cristian Gallardo-Cortes (Fish & Shellfish Immunology, 2025)

Trans-chalcone affects schistosomula and adult worms by impairing membrane integrity and attenuates the effects of Schistosoma mansoni-induced liver fibrosis - Mariana Barbosa Detoni; Luryan Silvério Fidélis Ortiz; Amanda Caroliny Gomilde; Bruna Taciane da Silva Bortoleti; Fernanda Tomiotto-Pellissier; Virgínia Marcia Concato-Lopes; Manoela Daiele Gonçalves-Lens; Taylon Felipe Silva; Ana Carolina Jacob Rodrigues; Amanda Cristina Machado Carloto; Ellen Mayara Souza Cruz; Danielle Lazarin-Bidóia; et al. (Chemico-Biological Interactions, 2025)

Geochemical processes influencing As distribution in waters associated with volcanic-hydrothermal systems: A case study of Coconucos volcanic chain-Puracé volcano, Colombia - Edgar Omar Almeida Miranda; Claudio Inguaggiato; Luisa Fernanda Meza Maldonado; Loïc Peiffer; Benedetto Schiavo; Gilles Levresse (Journal of South American Earth Sciences, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Effects of Long-Term Fluoride Exposure: Systematic Review and Meta-Analysis on Anxiety and Depression in Animal Models - Fernanda Marlen Enríquez-Sánchez; María Isabel Pérez-Vega; María de la Luz Miranda-Beltrán; Liliana Valdez-Jiménez (Biological Trace Element Research, 2025)

Mammary neoplasms in male dogs: A 24-year descriptive study - Fernanda Freitas Miranda; Lize Amanda Basaglia Borges; Karen Yumi Ribeiro Nakagaki; Camila Costa Abreu; Geovanni Dantas Cassali (Topics in Companion Animal Medicine, 2025)

Phytotoxicity of Hesperozygis ringens (Benth.) Epling essential oil on Bidens pilosa L. and Paspalum notatum Flüggé - Fernanda Bruxel; Amanda Pastório Borges; Amanda Janner Marques; Marcos Vinicius Vizioli Klaus; Mara Cíntia Winhelmann; Alex Dapont; Camila Thais Scheibler; Shirley Martins Silva; Lucélia Hoehne; Eduardo Miranda Ethur; Elisete Maria de Freitas (Biocatalysis and Agricultural Biotechnology, 2025)

Unraveling the unique and associated physiological challenges of iron, manganese and arsenic on Pistia stratiotes L. for phytoremediation of multi-contaminated water - Daniel Gomes Coelho; Vinícius Melo da Silva; Auxiliadora Oliveira Martins; Hugo Humberto de Araújo; Rafael de Souza Miranda; Elias Feitosa Araújo; Victor Issamu Uesugi; Fernanda dos Santos Farnese; Wagner L. Araújo; Juraci Alves de Oliveira (Science of The Total Environment, 2025)

Euploca flausinae (Heliotropiaceae), a new range-restricted endemic species from Central Brazil - José Iranildo Miranda de Melo; Fernanda Kelly Gomes da Silva; Dilma Maria de Brito Melo Trovão (Kew Bulletin, 2025)

Leaching potential of heavy metals and metalloids in mining-impacted soils of central Mexico: Accelerated column tests and geochemical modeling - Luisa Fernanda Rueda-Garzón; Alejandro Carrillo-Chávez; Raúl Miranda-Avilés; Maria Jesús Puy Alquiza; Gabriela Zanor; Margarita Ramírez-Ramírez; Carolina Muñoz-Torres; Pooja Kshirsagar; Yanmei Li; Xu Liao; Daniela Kristell Calvo-Ramos (Journal of South American Earth Sciences, 2025)

Bridging imaging-based in vitro methods from biomedical research to regulatory toxicology - Monica Piergiovanni; Milena Mennecozzi; Erio Barale-Thomas; Davide Danovi; Sebastian Dunst; David Egan; Aurora Fassi; Matthew Hartley; Philipp Kainz; Katharina Koch; Sylvia E. Le Dévédec; Iris Mangas; et al. (Archives of Toxicology, 2025)

Morphoanatomical and metabolic changes in Bixa orellana L. (Bixaceae) exposed to atmospheric fluorine - Thamires Fernanda Gomes; Franklin Patrocínio Rezende; Ademir Martins Lima; Genaina Aparecida de Souza; José Danizete Brás Miranda; Alice Pita Barbosa; Luzimar Campos da Silva (Environmental Science and Pollution Research, 2025)

Effects of the insecticide thiodicarb on non-target organs and behavior of the stingless bee Partamona helleri (Hymenoptera: Meliponini) - Davy Soares Gomes; Franciane Rosa Miranda; João Victor de Oliveira Motta; Mateus Soares de Oliveira; Cliver Fernandes Farder-Gomes; Daniel Silva Sena Bastos; Rodrigo Cupertino Bernardes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Hugo Bolsoni Zago; Cynthia Canêdo da Silva; Leandro Licursi de Oliveira; et al. (Pesticide Biochemistry and Physiology, 2025)

Taxonomic identity, but not evolutionary relatedness, determines the carbon stock and uptake of tropical forests trees - Alisson Borges Miranda Santos; Cléber Rodrigo de Souza; Fernanda Coelho de Souza; Natália de Aguiar-Campos; Vinicius Andrade Maia; Nathalle Cristine Alencar Fagundes; Aurélio de Jesus Rodrigues Pais; Gabriela Gomes Pires; Mariana Caroline Moreira Morelli; Jean Daniel Morel; Rubens Manoel dos Santos (Acta Oecologica, 2025)

Invasive dynamics of the signal crayfish Pacifastacus leniusculus in a protected area - Francisco Carvalho; Henrique Alves; Cláudia Pascoal; Paulo Castro; Fernando Miranda; Amílcar Teixeira; Fernanda Cássio; Ronaldo Sousa (Hydrobiologia, 2025)
Invasive species have been drivers of biodiversity loss and functional changes in aquatic ecosystems, including in protected areas. Therefore, monitoring population invasion dynamics and biological traits is fundamental to better understand their ecological and economic impacts and for management actions development. We followed signal crayfish ( Pacifastacus leniusculus ) invasion in Rabaçal River upper reach at Montesinho Natural Park, Portugal. We collected information on the spread and biological traits (abundance, size, weight, physical condition, sex ratio, and aggressiveness) to assess differences between invasion core and front areas and among years. Signal crayfish population remained restricted since first reports in 2013 in the invasion core until 2017. After 2019, signal crayfish population has been spreading downstream, decreasing abundance at invasion core but increasing at invasion front. Significant higher number of crayfish with claw loss indicate potential higher signs of aggressiveness in the invasion front. Results also demonstrate a significant dominance of females although sex ratio is closer to 1:1 at the invasion front. Overall, results indicate signal crayfish is spreading and increasing their abundance at Rabaçal River highlighting the need for immediate management actions to hold dispersion and mitigate possible impacts.

“Together is better”: the contribution of academy, citizen science and gray literature for the knowledge of the urban avifauna of a megadiverse easternmost Amazonian ecotonal border - Sara Miranda Almeida; Gustavo Gonsioroski; Nubia Carla Santos Marques; Fernanda Guimarães Fava; João Marcelo da Silva Abreu; Letícia Gomes da Silva; Rafaela Velloso Missagia; Vanessa Guimarães Lopes; Verônica Maria de Oliveira; Erick Cristofore Guimarães; Pedro Walfir M. Souza-Filho; Valéria da Cunha Tavares (Ornithology Research, 2025)

Effects of brushing dairy calves on behaviour, physiology and genes expression - Karolini Tenffen De-Sousa; Catiúcia Oliveira Miranda; João Alberto Negrão; Aníbal Eugênio Vercesi Filho; Marcia Saladini Vieira Salles; Flavia Fernanda Simili; Lenira El Faro (Applied Animal Behaviour Science, 2025)

CRISPR-Cas systems in enterococci - Amanda Seabra Cabral; Fernanda de Freitas Lacerda; Vitor Luis Macena Leite; Filipe Martire de Miranda; Amanda Beiral da Silva; Bárbara Araújo dos Santos; Jailton Lobo da Costa Lima; Lúcia Martins Teixeira; Felipe Piedade Gonçalves Neves (Brazilian Journal of Microbiology, 2024)

The cultivation of Lippia dulcis under ChromatiNet induces changes in vegetative growth, anatomy and essential oil chemical composition - Fernanda Naiara Santos Ribeiro; Rafael Marlon Alves de Assis; Jeremias José Ferreira Leite; Thayane Ferreira Miranda; Eduardo Alves; Suzan Kelly Vilela Bertolucci; Jose Eduardo Brasil Pereira Pinto (South African Journal of Botany, 2024)

Effect of a thiohydantoin salt derived from -Arginine on Leishmania amazonensis and infected cells: Insights from biological effects to molecular docking interactions - Bruna Taciane da Silva Bortoleti; Priscila Goes Camargo; Manoela Daiele Gonçalves; Fernanda Tomiotto-Pellissier; Taylon Felipe Silva; Virginia Marcia Concato; Mariana Barbosa Detoni; Danielle Larazin Bidóia; Camilo Henrique da Silva Lima; Carlos Rangel Rodrigues; Marcelle de Lima Ferreira Bispo; Fernando Cesar de Macedo; et al. (Chemico-Biological Interactions, 2024)

Metabolic consequences of interesterified palm oil and PCB-126 co-exposure in C57BL/6 mice - Ananda Vitoria Silva Teixeira; Fernanda Torres Quitete; Bruna Cadete Martins; Thamara Cherem Peixoto; Mayara da Silva Ribeiro; Patricia Coelho de Velasco; Caroline Miranda; Angela de Castro Resende; Daniela Caldeira Costa; Geórgia Correa Atella; Daniela de Barros Mucci; Vanessa Souza-Mello; et al. (Food and Chemical Toxicology, 2024)

Evapotranspiration and crop coefficient of ‘Kent’ mango in an important fruit‐growing hub in Brazil - Marcelo José da Silva; Magna Soelma Beserra de Moura; Herica Fernanda de Sousa Carvalho; Cloves Vilas Boas dos Santos; Mário de Miranda Villas Boas Ramos Leitão; Luis Fernando de Souza Magno Campeche; Thieres George Freire da Silva (Irrigation and Drainage, 2024)
The ‘Kent’ mango is one of the main cultivars produced in the São Francisco valley. However, due to a lack of data, water management was carried out using coefficients from the Tommy Atkins cultivar. Thus, aiming to achieve greater water management efficiency, the aim of this study was to evaluate the growth, radiation and energy balance, evapotranspiration and coefficients of the ‘Kent’ mango in the lower‐middle São Francisco valley in Brazil. The study was conducted in an orchard over two harvests between 2017 and 2018. The radiation and energy balance, evapotranspiration (ET c ) and crop coefficients ( K c ) of the mango were estimated from micrometeorological data. The mean reference evapotranspiration (ET 0 ) and ET c values were 5.47 and 4.40 mm day −1 (vegetative growth, VG), 4.42 and 4.29 mm day −1 (floral induction, FI), 4.08 and 3.48 mm day −1 (floral induction + flowering, FI + FL), 4.51 and 3.63 mm day −1 (fruit drop, FD) and 6.09 and 4.46 mm day −1 (formation fruit + maturation fruit phase, FF + MF). Under the climate conditions of the São Francisco valley, K c values of 0.80, 0.97, 0.85, 0.80 and 0.74 are recommended for the ‘Kent’ mango during the VG, FI, FI + FL, FD and FF + MF phases, respectively.

Exposure to the herbicide tebuthiuron affects behavior, enzymatic activity, morphology and physiology of the midgut of the stingless bee Partamona helleri - Cliver Fernandes Farder-Gomes; Franciane Rosa Miranda; Rodrigo Cupertino Bernardes; Daniel Silva Sena Bastos; Davy Soares Gomes; Fernanda Pereira da Silva; Pollyana Leão Gonçalves; Stella Arndt; André da Silva Xavier; Hugo Bolsoni Zago; José Eduardo Serrão; Gustavo Ferreira Martins; et al. (Environmental Toxicology and Pharmacology, 2024)

Using Electrical Resistivity Tomography to Understand the Hydrogeological Behavior of Acid Drainage Percolation in a Fractured Aquifer at a Uranium Mining Site - César Augusto Moreira; Leonides Guireli Netto; Fernanda Miranda de Siqueira Buchi; Marco Antônio Fontoura Hansen; Henri Masquelin; José Pedro Rebés Lima (Mine Water and the Environment, 2024)

Correction to: Efficient Adsorption of Lead(II) Ions from Artificial Wastewater by Organically Tailored vs TEOS‑Doped Silica Aerogels: Synthesis, Characterization and Isotherm Studies - Faheem Akhter; Heera Lal Soni; Abdul Rauf Jamali; Fernanda Miranda Zoppas; Sobhy M. Ibrahim (Water, Air, & Soil Pollution, 2024)

Beta diversity and regionalization of the western Atlantic marine biota - Ubirajara Oliveira; Fernanda Azevedo; Alan Dias; Ana Carolina Sousa de Almeida; André R. Senna; Antonio C. Marques; Dafinny Rezende; Eduardo Hajdu; Erick Alves Pereira Lopes‐Filho; Fábio Bettini Pitombo; Gabriela Moura de Oliveira; João Gabriel Doria; et al. (Journal of Biogeography, 2024)
Aim Understanding the factors determining marine community variations is important for biogeography and conservation. Beta diversity is a metric for mapping species composition variations between communities and regionalizing biota. Ecoregions are commonly used for regionalization, but their empirical testing has been limited. Our aim is to map marine species composition variations in the Western Atlantic, identify variables related to these variations, and regionalize areas based on community distribution. Additionally, we test whether currently proposed ecoregions represent unique biota units and specific environmental conditions. Location Western Atlantic Ocean. Taxon Vertebrates, invertebrates and algae. Methods We constructed a large marine biodiversity database, including vertebrates, invertebrates, and algae, totalling over 4 million records. We used the generalized dissimilarity model (GDM) to identify variables most related to species composition variations and map beta‐diversity variations. We employed an unsupervised classifier for community regionalization. To test if the ecoregion regionalization boundaries are corroborated by species distribution data, we used the Sørensen index. To assess if ecoregions correspond to environmental units, we checked if areas had distinct environmental conditions using a PCA of 134 marine environmental variables. Results The GDM explained a high variation in species composition, 61% in the complete database. Analysing vertebrates, invertebrates and algae separately also yielded relatively high results: 46%, 54%, and 33%, respectively. Coastal areas differed from open sea areas in composition. Environmental variables combined better explained beta diversity than isolated variables. The regionalization based on GDM was not congruent with ecoregion boundaries. Moreover, ecoregions showed no distinction in species composition or environmental conditions. Main Conclusions This study's regionalization is crucial for marine biodiversity conservation, focusing on understanding species composition patterns between coastal and open sea areas to develop tailored conservation strategies. Despite sampling limitations, the study advances marine biogeography knowledge by analysing over 4 million species records and 134 environmental variables. This comprehensive approach enhances understanding marine species distribution and diversity and aiding the development of effective conservation measures.

Innovative pathways for ethanol production: Harnessing xylose’s bioenergy potential using Brazilian wild isolated yeasts - Marcus Vinicius Astolfo da Costa; Ana Carolina Rodrigues Sousa; Arthur Gasseta Batista; Fernanda Elisa Gomes Miranda Paula; Marita Vedovelli Cardozo; Sarah Regina Vargas; Rafael Rodrigues Philippini; Caio Roberto Soares Bragança (Bioresource Technology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Unraveling DEHP influence on hemoglobin S polymerization in sickle cell disease: Ex vivo, in vitro and in silico analysis - Rodrigo Abreu Camacho; Aghata Vitoria Machado; Fernanda de Oliveira Mendonça; Lyzes Rosa Teixeira-Alves; Camila Cristina Guimarães-Nobre; Evelyn Mendonça-Reis; Priscila Ferreira da Silva; Thyago R. Cardim-Pires; Leandro Miranda-Alves; Clemilson Berto-Junior (Toxicology in Vitro, 2024)

Comparison of in vitro toxicity in HepG2 cells: Toxicological role of Tebuconazole-tert-butyl-hydroxy in exposure to the fungicide Tebuconazole - Fernanda Gomes Leite; Clara de Paula Marques Silva; Raul Ghiraldelli Miranda; Daniel Junqueira Dorta (Pesticide Biochemistry and Physiology, 2024)

Chemical characterization and antimicrobial activity of Baccharis vulneraria Baker essential oil against strains of microorganisms that cause cutaneous infections - Kétlin Fernanda Rodrigues; Daiane Heidrich; Fernanda Fensterseifer; Manoela Teixeira Roso; Fernanda Bruxel; Eduardo Miranda Ethur; Lucélia Hoehne; Elisete Maria de Freitas (Natural Product Research, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

The Phenotypic Spectrum of Spinocerebellar Ataxia Type 19 in a Series of Latin American Patients - Diana Avila-Jaque; Fernanda Martin; M. Leonor Bustamante; Mariana Luna Álvarez; José Manuel Fernández; David José Dávila Ortiz de Montellano; Rosa Pardo; Diego Varela; Marcelo Miranda (The Cerebellum, 2024)

Effect of low-glucosinolate crambe meal in diet on lactational performance, efficiency of nutrient utilization, and hepatic function of crossbred Holstein × Zebu and Jersey cows - Daiane Caroline de Moura; Flavio Junior Gonçalves Vieira; Robson Moreira Miranda; Poliana Oliveira Cordeiro; Luana Molossi; Danielly da Silva Souza; Viviane Helena Zampieri; Suziane Rodrigues Soares; Fernanda Norberto Viana; André Fonseca de Brito; André Soares de Oliveira (Tropical Animal Health and Production, 2023)

Expansion of marine pollution along the coast: Negative effects on kelps and contamination transference to benthic herbivores? - Loretto Contreras-Porcia; Andrés Meynard; Cristian Bulboa; Paulina Vargas; Jorge Rivas; Nicolás Latorre-Padilla; Sergio A. Navarrete; Francesca V. Search; Carolina Oyarzo-Miranda; Fernanda Toro-Mellado (Marine Environmental Research, 2023)

Assessments of Pollution Status and Human Health Risk of Potentially Toxic Elements in Primary Crops and Agricultural Soils in Guanajuato, Mexico - Xu Liao; Yanmei Li; Raúl Miranda-Avilés; María Jesús Puy-Alquiza; Jianmin Bian; Jesús Horacio Hernández Anguiano; Alma Hortensia Serafín Muñoz; Saugata Datta; Xiaoxiao Zha; Jianli Liu; Daniela Moncada; Zhiqing Zhao; et al. (Water, Air, & Soil Pollution, 2023)

A suitable model to investigate acute neurological consequences of coronavirus infection - Jordane Pimenta; Bruna Da Silva Oliveira; Anna Luiza Diniz Lima; Caroline Amaral Machado; Larisse De Souza Barbosa Lacerda; Leonardo Rossi; Celso Martins Queiroz-Junior; Luiz Pedro De Souza-Costa; Ana Claudia Santos Pereira Andrade; Matheus Rodrigues Gonçalves; Bárbara Mota; Fernanda Martins Marim; et al. (Inflammation Research, 2023)

Spatial marine meiofauna variations in areas undergoing different disturbance levels on the Amazon coast - Marcos Eduardo Miranda Santos; Tamires Costa Silva; Jeyce Kelly Ferreira Sirqueira; Maira Wilson Paiva Gonçalves; Geanderson Morais Santos; Kelly Fernanda de Sousa Santos; Jorge Luiz Silva Nunes (Biologia, 2023)

Rosuvastatin enhances alterations caused by Toxoplasma gondii in the duodenum of mice - Nelson Raimundo de Miranda Júnior; Amanda Gubert Alves dos Santos; Andréia Vieira Pereira; Isabela Alessandra Mariano; Ana Lucia Falavigna Guilherme; Priscilla de Laet Santana; Lucimara de Fátima Beletini; Fernanda Ferreira Evangelista; Gessilda de Alcantara Nogueira-Melo; Debora de Mello Gonçales Sant'Ana (Tissue and Cell, 2023)

Influence of species invasion, seasonality, and connectivity on fish functional and taxonomic beta-diversity in a Neotropical floodplain - Matheus Henrique Ferreira Aleixo; Fernanda Moreira Florêncio; Fernando Miranda Lansac-Tôha; Bárbara Angélio Quirino; Rosemara Fugi (Biological Invasions, 2023)

Alkylamides from Acmella oleracea : antinociceptive effect and molecular docking with cannabinoid and TRPV1 receptors - Raíssa M. Kao Yien; Anne Caroline C. Gomes; Rodolfo Goetze Fiorot; Ana Luísa Palhares Miranda; Gilda A. Neves; Brenda da Silva Andrade; Fernanda N. Costa; Jorge Luiz Mendonça Tributino; Naomi Kato Simas (Natural Product Research, 2023)

Bj-PRO-10c, as an allosteric regulator of argininosuccinate synthase, is a potential therapy for neuroblastoma metastasis - Fernanda Coutinho; Lara MF. Guimarães; Rodrigo Seeger; Ana Paula J Santos; Talita Glaser; Denise Yamamoto; Lucas Lacerda; Vanessa Arnaud-Sampaio; Caio VT. Rossini; Izadora Rabelo; Nathália Miranda de Medeiros; Daniela Ramos Truzzi; et al. (Toxicon, 2023)

Assessing the ecophysiological effects of iron mining tailings on velvet bean: implications for growth limitations based on mineral composition and physicochemical properties of tailings-soil substrates - Jober Condé Evangelista Freitas; Cristiano Ferrara de Resende; Maria de Paula Pimenta; Laís Manço Frattini; Paola Ramos Coutinho Reis; Janaína Barros Miranda; Júlio César José da Silva; Dionéia Evangelista César; Fernanda Carlota Nery; Paulo Henrique Pereira Peixoto (Brazilian Journal of Botany, 2023)

Post-thaw addition of pentoxifylline to equine semen previously cryopreserved with different concentrations of cholesterol-loaded cyclodextrin - Virginia Maria Toledo Vilela; Lorena Leticia Oliveira Gomes; Juliana Horta Wilke Diniz; Thayná Grazielle Rodrigues Miranda; Bárbara Calefo Toyama; Deborah Freitas Silva; Pedro Thomaz Ladislau; Anna Julia Oliveira; Fernanda Saules Ignácio; Gabriel Augusto Monteiro (Journal of Equine Veterinary Science, 2023)

Effect of FertTalp addition to stallion semen on kinetic parameters and production of intracellular hydrogen peroxide after thawing - Virginia Maria Toledo Vilela; Thayná Grazielle Rodrigues Miranda; Lorena Leticia Oliveira Gomes; Juliana Horta Wilke Diniz; Bárbara Calefo Toyama; Deborah Freitas Silva; Pedro Thomaz Ladislau; Fernanda Saules Ignácio; Gabriel Augusto Monteiro (Journal of Equine Veterinary Science, 2023)

Doppler evaluation of testicular arteries of stallions of different ages - Deborah Freitas Silva; Debora Passagli Barbosa; Janaina de Paula Rodrigues; Thayná Grazielle Rodrigues Miranda; Virginia Maria Toledo Vilela; Pedro Thomaz Ladislau; Fernanda Saules Ignácio; Gabriel Augusto Monteiro (Journal of Equine Veterinary Science, 2023)

Hemodynamic evaluation of the testicular artery in stallions with spermatic cord torsion - Deborah Freitas Silva; Debora Passagli Barbosa; Janaina de Paula Rodrigues; Thayná Grazielle Rodrigues Miranda; Virginia Maria Toledo Vilela; Fernanda Saules Ignácio; Gabriel Augusto Monteiro (Journal of Equine Veterinary Science, 2023)

Effect of cholesterol inclusion on kinetics, mitochondrial potential and membrane stability of equine spermatozoa after thawing - Thayná Grazielle Rodrigues Miranda; Virginia Maria Toledo Vilela; Lorena Leticia Oliveira Gomes; Juliana Horta Wilke Diniz; Bárbara Calefo Toyama; Deborah Freitas Silva; Pedro Thomaz Ladislau; Fernanda Saules Ignácio; Gabriel Augusto Monteiro (Journal of Equine Veterinary Science, 2023)

Correction to: Dopamine removal from water by advanced oxidative processes with Fe/N‑doped carbon nanotubes - Anaí Laurel Leon; Nicolas Alejandro Sacco; Fernanda Miranda Zoppas; Rosario Galindo; Emilio Muñoz Sandoval; Fernanda Albana Marchesini (Environmental Science and Pollution Research, 2023)

Tocotrienols-enriched Self-nanoemulsifying Drug Delivery System Enhances the Antileukemic Activity of All-trans Retinoic Acid but not Electrocardiogram Alterations Evoked by Its Combination with Arsenic Trioxide - Gabriel Silva Marques Borges; Pierre Sicard; Cristina de Mello Gomides Loures; Fernanda Gontijo Cristina Evangelista; Camila Campos Sales; Adriano de Paula Sabino; Christian Fernandes; Lucas Antônio Miranda Ferreira; Sylvain Richard (AAPS PharmSciTech, 2023)

Dopamine removal from water by advanced oxidative processes with Fe/N-doped carbon nanotubes - Anaí Laurel Leon; Nicolas Alejandro Sacco; Fernanda Miranda Zoppas; Rosario Galindo; Emilio Muñoz Sandoval; Fernanda Albana Marchesini (Environmental Science and Pollution Research, 2023)

Efficient Adsorption of Lead(II) Ions from Artificial Wastewater by Organically Tailored vs TEOS-Doped Silica Aerogels: Synthesis, Characterization and Isotherm Studies - Faheem Akhter; Heera Lal Soni; Abdul Rauf Jamali; Fernanda Miranda Zoppas; Sobhy M. Ibrahim (Water, Air, & Soil Pollution, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Estimation of genetic parameters and inbreeding depression in Piau pig breed - Letícia Fernanda de Oliveira; Paulo Sávio Lopes; Layla Cristien Cássia Miranda Dias; Leandro Magno Dornelas e Silva; Hugo Teixeira Silva; Simone Eliza Facioni Guimarães; Daniele Botelho Diniz Marques; Delvan Alves da Silva; Renata Veroneze (Tropical Animal Health and Production, 2023)

Seaweed restocking along the Chilean coast: History, present, and inspiring recommendations for sustainability - Carolina Oyarzo-Miranda; Ricardo Otaíza; Alexis Bellorín; J.M. Alonso Vega; Fadia Tala; Nelson A. Lagos; Fernanda X. Oyarzún; Rodrigo A. Estévez; Nicolás Latorre-Padilla; Ana María Mora Tapia; Luis Figueroa-Fábrega; Roddy Jara-Yáñez; et al. (Frontiers in Marine Science, 2023)
Several seaweed species are commercialized worldwide both due to high demand for food and feed and as a raw material for the extraction of phycocolloids such as agar, carrageenan, and alginates that are used broadly in the food, cosmetic, and pharmaceutical industries. Chile is the world’s leading marine seaweed biomass producer when it comes to the exploitation of natural kelp beds. This extraction pressure has persisted for decades and has resulted in a reduction in natural stocks along the benthic ecosystems of the Chilean coast. Over the last three decades, several strategies aimed at restoring seaweed stocks have been implemented (i.e., sexual and asexual reproduction, the use of spore-type propagules or fragments of thalli, and entire thallus transplants). Success rates have varied, but the biological feasibility of such strategies has been demonstrated for several species. However, technological improvements must be achieved to move from small-scale, pilot experiments to cost-effective restocking strategies that are easy to transfer to fisher communities and another end-user, scalable to marine field conditions, and socio-ecologically sustainable. Researchers in other geographic areas have explored similar pathways for developing kelp restocking strategies and have tackled the research gaps regarding its massification. This work summarizes the research activities carried out in recent decades in the search for sustainable strategies to restore algal stocks in Chile.

Analysis of the influence of wheat residues on gypsum composites - Diogo Antonio Correa Gomes; Eduardo Hélio de Novais Miranda; Fernanda Carolina Resende; Denisse Concepción Vega Villarruel; Lourival Marin Mendes; José Benedito Guimarães Júnior (Innovative Infrastructure Solutions, 2023)

Plant Litter from Rare Species Increases Functional Diversity and Decomposition of Species Mixtures - Raiane S. Rabelo; Alan M. Tonin; Luz Boyero; Fernanda G. G. Miranda; Patrícia P. Gomes; Paulino Bambi; Guilherme Sena; José F. Gonçalves Júnior (Ecosystems, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Interference effects of oxyanions commonly found in natural waters on the catalytic reduction of nitrate in water - Nicolás Alejandro Sacco; Fernanda Miranda Zoppas; Thiago Favarini Beltrame; Eduardo Ernesto Miró; Fernanda Albana Marchesini (Environmental Science and Pollution Research, 2022)

Contamination assessment and potential sources of heavy metals and other elements in sediments of a basin impacted by 500 years of mining in central Mexico - Luisa Fernanda Rueda-Garzon; Raúl Miranda-Avilés; Alejandro Carrillo-Chávez; María Jesus Puy-Alquiza; Jorge Luis Morales-Martinez; Gabriela Zanor (Environmental Monitoring and Assessment, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Animal thermal comfort index for the state of Paraíba, Brazil: trend, influencing factors, and mitigating measures - Valquiria Cordeiro da Silva; Robson de Sousa Nascimento; José Pinheiro Lopes Neto; Fernanda Fernandes de Melo Lopes; Jaciara Ribeiro Miranda; Dermeval Araújo Furtado (Theoretical and Applied Climatology, 2022)

Role of inflammation and oxidative stress in tissue damage associated with cystic fibrosis: CAPE as a future therapeutic strategy - Victor Emanuel Miranda Soares; Thiago Inácio Teixeira do Carmo; Fernanda dos Anjos; Jonatha Wruck; Sarah Franco Vieira de Oliveira Maciel; Margarete Dulce Bagatini; Débora Tavares de Resende e Silva (Molecular and Cellular Biochemistry, 2022)

Predicting the Invasion Risk by Anastrepha sororcula (Diptera: Tephritidae) in Distinct Geographic Regions - Adriane Vieira Souza; Elder Assis Miranda; Joseane Fernanda Passos; Elton Lucio Araujo; Clarice Diniz Alvarenga; Janisete Gomes Silva (Neotropical Entomology, 2021)

Cytogenetic and Physicochemical Effects of Road Structure Construction on Trincheira River’s Water - Bruna Cardozo; Emerson R. Santos; Fernanda Barizon; Luiz A. Bertassi Miranda; Raul A. Gross; Fernando C. Manosso; Elisângela Düsman (Water, Air, & Soil Pollution, 2021)

Dietary nutrient restrictions in the post-weaning period change Santa Inês ewe lamb nutritional metabolic profile - Clésio dos Santos Costa; Marcos Cláudio Pinheiro Rogério; Alexandre Lima Ferreira; Fernanda Samarini Machado; Roberto Cláudio Fernandes Franco Pompeu; Francisco Gleyson da Silveira Alves; João Paulo Arcelino do Rêgo; Patrícia Guimarães Pimentel; James Pierre Muir; José Neuman Miranda Neiva (Tropical Animal Health and Production, 2021)

Hyperinflammation and airway surface liquid dehydration in cystic fibrosis: purinergic system as therapeutic target - Thiago Inácio Teixeira do Carmo; Victor Emanuel Miranda Soares; Jonatha Wruck; Fernanda dos Anjos; Débora Tavares de Resende e Silva; Sarah Franco Vieira de Oliveira Maciel; Margarete Dulce Bagatini (Inflammation Research, 2021)

Assessing the viability of electro-absorption and photoelectro-absorption for the treatment of gaseous perchloroethylene - Martín Muñoz-Morales; Montse Castañeda-Juárez; Fernanda Lourdes Souza; Cristina Saez; Pablo Cañizares; Verónica Martínez-Miranda; Ivonne Linares-Hernández; Manuel Andrés Rodrigo (Environmental Science and Pollution Research, 2021)

HIV-Associated Cryptococcal Meningitis Patients Treated with Amphotericin B Deoxycholate Plus Flucytosine under Routine Care Conditions in a Referral Center in São Paulo, Brazil - José E. Vidal; Camila de Albuquerque Moraes; Renata Elisie Barbalho de Siqueira; Nathalya Fernanda Brito Miranda; Rosa Marcusso; David R. Boulware; Augusto C. Penalva de Oliveira (Mycopathologia, 2021)

Genetic Connectivity of the West Indian Manatee in the Southern Range and Limited Evidence of Hybridization With Amazonian Manatees - Fábia de Oliveira Luna; Caitlin E. Beaver; Coralie Nourisson; Robert K. Bonde; Fernanda L. N. Attademo; Adriana Vieira Miranda; Juan Pablo Torres-Florez; Glaucia Pereira de Sousa; José Zanon Passavante; Margaret E. Hunter (Frontiers in Marine Science, 2021)
The Antillean subspecies of the West Indian manatee is classified as endangered by the International Union for the Conservation of Nature (IUCN) Red List. In Brazil, the manatee population is listed as endangered with an estimated population size of 500–1,000. Historic hunting, recent habitat degradation, and fisheries bycatch have decreased the population size. The Amazonian manatee is listed as vulnerable by the IUCN with unknown population sizes within Brazil. The Antillean manatee occurs in sympatry with the Amazonian manatee in Brazil and hybridization has been previously indicated. To provide information on the genetic structure, diversity, and degree of hybridization in the sympatric zone near the Amazon River mouth, the mitochondrial DNA control region and 13 nuclear microsatellite markers were assessed on the two species. Samples were analyzed from the Antillean subspecies across its distribution in Brazil ( n = 78) and from the Amazonian species ( n = 17) at the Amazon River mouth and inland mainstem river. To assess the previously defined evolutionary significant units of Antillean manatees in the area, an additional 11 samples from Venezuela and Guyana were included. The Antillean manatee was found to be a single population in Brazil and had lower than average number of alleles (3.00), expected heterozygosity (0.34), and haplotype diversity (0.15) when compared to many other manatee populations. The low values may be influenced by the small population size and extended pressures from anthropogenic threats. Gene flow was identified with Venezuela/Guyana in admixed Antillean Brazil samples, although the two populations were found to be moderately divergent. The nuclear loci in Venezuela/Guyana Antillean manatee samples indicated high differentiation from the samples collected in the Amazon River ( F ST = 0.35 and R ST = 0.18, p = 0.0001). No indication of nuclear hybridization was found except for a single sample, “Poque” that had been identified previously. The distribution of Antillean manatees in Brazil is extensive and the areas with unique habitat and threats would benefit from independent management and conservation actions. Gene flow, resulting in genetic diversity and long-term population stability, could be improved in the southern range through habitat restoration, and the establishments of travel corridors and protected areas, which are particularly important for successful parturition and neonatal calf survival.

Superficial properties of activated carbon fiber catalysts produced by green synthesis and their application in water purification - Fernanda Miranda Zoppas; Thiago Favarini Beltrame; Florencia Agustina Sosa; Andrea Moura Bernardes; Eduardo Miró; Fernanda Albana Marchesini (Environmental Science and Pollution Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Major mutations in the NS3 gene region of hepatitis C virus related to the resistance to direct acting antiviral drugs: a systematic review - Ana Elisa de Figueiredo Miranda Mundim; Fernanda de Oliveira Feitosa de de Castro; Marina Brandão Braz Albuquerque; Cesar Augusto Sam Tiago Vilanova-Costa; Irmtraut Araci Hoffmann Pfrimer; Antonio Márcio Teodoro Cordeiro Silva (VirusDisease, 2020)

Lower cost alternatives for molecular diagnosis of COVID-19: conventional RT-PCR and SYBR Green-based RT-qPCR - Erick Gustavo Dorlass; Cairo Oliveira Monteiro; Amanda Oliveira Viana; Camila Pereira Soares; Rafael Rahal Guaragna Machado; Luciano Matsumiya Thomazelli; Danielle Bastos Araujo; Fabyano Bruno Leal; Erika Donizette Candido; Bruna Larotonda Telezynski; Camila Araujo Valério; Vanessa Nascimento Chalup; et al. (Brazilian Journal of Microbiology, 2020)

Effect of arginine on microorganisms involved in dental caries: a systematic literature review of in vitro studies - Marina Lins Miranda; Bianca Núbia Souza Silva; Karina Borges Salomão; Analú Barros de Oliveira; Paulo Roberto Gabbai-Armelin; Fernanda Lourenção Brighenti (Biofouling, 2020)

Antifungal activity of Copaíba resin oil in solution and nanoemulsion against Paracoccidioides spp. - Lívia do Carmo Silva; Meire Ane Costa Miguel Miranda; Julianna Veiga de Freitas; Sarah Fernanda Araújo Ferreira; Emília Celma de Oliveira Lima; Cecilia Maria Alves de Oliveira; Lucilia Kato; Ana Paula Terezan; Anselmo Fortunato Ruiz Rodriguez; Fernando Sergio Escócio Drumond Via Faria; Célia Maria de Almeida Soares; Maristela Pereira (Brazilian Journal of Microbiology, 2020)

Use of a two-step process to denitrification of synthetic brines: electroreduction in a dual-chamber cell and catalytic reduction - Thiago Favarini Beltrame; Fernanda Miranda Zoppas; Luciano Marder; Fernanda Albana Marchesini; Eduardo Miró; Andrea Moura Bernardes (Environmental Science and Pollution Research, 2020)

Spatial and Seasonal Distribution of Holochilus sciureus with Schistosoma mansoni Infection in an Endemic Area for Schistosomiasis in Brazil - Carla Fernanda do Carmo-Silva; Andrea Teles-Reis; Raynara Fernanda Silva-Soares; João Gustavo Mendes Rodrigues; Maria Gabriela Sampaio Lira; Ranielly Araújo Nogueira; Davi Viegas-Melo; Diogo Tavares Cardoso; Guilherme Silva Miranda; Nêuton Silva-Souza (Acta Parasitologica, 2019)

Pravastatin and Simvastatin Pretreatment in Combination with Pyrimethamine and Sulfadiazine Reduces Infection Process of Toxoplasma gondii Tachyzoites (RH Strain) in HeLa Cells - Raquel Arruda da Silva Sanfelice; Suelen Santos da Silva; Larissa Rodrigues Bosqui; Lais Fernanda Machado; Milena Menegazzo Miranda-Sapla; Luciano Aparecido Panagio; Italmar Teodorico Navarro; Ivete Conchon-Costa; Wander Rogério Pavanelli; Ricardo Sergio Almeida; Idessania Nazareth Costa (Acta Parasitologica, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Spongivory by Fishes on Southwestern Atlantic Coral Reefs: No Evidence of Top-Down Control on Sponge Assemblages - Fernanda L. Lorders; Ricardo J. Miranda; José Anchieta C. C. Nunes; Francisco Barros (Frontiers in Marine Science, 2018)

Herbivory effects on the periphytic algal functional diversity in lake ecosystems: an experimental approach - Bárbara Dunck; Diogo Castanho Amaral; Ubirajara Lima Fernandes; Natália Fernanda Santana; Taise Miranda Lopes; Liliana Rodrigues (Hydrobiologia, 2018)

Anthropogenic disturbances influencing ciliate functional feeding groups in impacted tropical streams - Bianca Trevizan Segovia; Fernando Miranda Lansac-Toha; Bianca Ramos de Meira; Adalgisa Fernanda Cabral; Fabio Amodêo Lansac-Tôha; Luiz Felipe Machado Velho (Environmental Science and Pollution Research, 2016)

Exogenous nitric oxide improves sugarcane growth and photosynthesis under water deficit - Neidiquele M. Silveira; Lucas Frungillo; Fernanda C. C. Marcos; Milena T. Pelegrino; Marcela T. Miranda; Amedea B. Seabra; Ione Salgado; Eduardo C. Machado; Rafael V. Ribeiro (Planta, 2016)

Insights from genome of Clostridium butyricum INCQS635 reveal mechanisms to convert complex sugars for biofuel production - Thiago Bruce; Fernanda Gomes Leite; Milene Miranda; Cristiane C. Thompson; Nei Pereira; Mariana Faber; Fabiano L. Thompson (Archives of Microbiology, 2016)

High sugar and butter (HSB) diet induces obesity and metabolic syndrome with decrease in regulatory T cells in adipose tissue of mice - Tatiani Uceli Maioli; Juliana Lauar Gonçalves; Mariana Camila Gonçalves Miranda; Vinícius Dantas Martins; Laila Sampaio Horta; Thais Garcias Moreira; Ana Lucia Brunialti Godard; Andrezza Fernanda Santiago; Ana Maria Caetano Faria (Inflammation Research, 2016)

Effect of Zinc Supplementation on Antioxidant Defenses and Oxidative Stress Markers in Patients Undergoing Chemotherapy for Colorectal Cancer: a Placebo-Controlled, Prospective Randomized Trial - Sofia Miranda de Figueiredo Ribeiro; Camila Bitu Moreno Braga; Fernanda Maris Peria; Fernanda Aparecida Domenici; Edson Zangiacomi Martinez; Omar Feres; José Joaquim Ribeiro da Rocha; Selma Freire de Carvalho da Cunha (Biological Trace Element Research, 2016)

Implications of the harvest time on Syngonanthus nitens (Bong.) Ruhland (Eriocaulaceae) management in the state of Minas Gerais - Maria Neudes Sousa de Oliveira; Sara Michelly Cruz; Amanda Miranda de Sousa; Fernanda da Conceição Moreira; Mário Kiichiro Tanaka (Brazilian Journal of Botany, 2014)

First Molecular Typing of Cryptococcemia-Causing Cryptococcus in Central-West Brazil - Rosianne Assis de Sousa Tsujisaki; Anamaria Mello Miranda Paniago; Manoel Sebastião da Costa Lima Júnior; Débora de Souza Olartechea de Alencar; Fernanda Luíza Espinosa Spositto; Maína de Oliveira Nunes; Luciana Trilles; Marilene Rodrigues Chang (Mycopathologia, 2013)

Erratum to: In vitro activities of plant extracts from the Brazilian Cerrado and Pantanal against Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - Carolina da Silva Barbosa; Ligia Miranda Ferreira Borges; José Nicácio; Reginaldo Dias Alves; Carlos Henrique Miguita; Ivana Maria Póvoa Violante; Lidilhone Hamerski; Walmir Silva Garcez; Fernanda Rodrigues Garcez (Experimental and Applied Acarology, 2013)

In vitro activities of plant extracts from the Brazilian Cerrado and Pantanal against Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - Carolina da Silva Barbosa; Ligia Miranda Ferreira Borges; José Nicácio; Reginaldo Dias Alves; Carlos Henrique Miguita; Ivana Maria Póvoa Violante; Lidilhone Hamerski; Walmir Silva Garcez; Fernanda Rodrigues Garcez (Experimental and Applied Acarology, 2013)

Identification of carotenoids with high antioxidant capacity produced by extremophile microorganisms - Fernanda Mandelli; Viviane S. Miranda; Eliseu Rodrigues; Adriana Z. Mercadante (World Journal of Microbiology and Biotechnology, 2012)

Oviposition by a moth suppresses constitutive and herbivore-induced plant volatiles in maize - M. Fernanda Gomes Villalba Peñaflor; Matthias Erb; Christelle Aurélie Maud Robert; Livia Atauri Miranda; Andrea Graf Werneburg; Fábio Cleisto Alda Dossi; Ted C. J. Turlings; J. Maurício Simões Bento (Planta, 2011)